Answer:
zeros : -3/2 , multiplicity = 1
1 , multiplicity = 2
Explanation:
![y=(2x +3)(x -1)^2](https://img.qammunity.org/2020/formulas/mathematics/high-school/okzq69sdi47vo23r7xi75wphywa9ao8wm7.png)
To find zeros we set each factor =0 and solve for x
2x+3 =0
subtract 3 on both sides
2x= -3
divide by 2 on both sides
x= -3/2
The exponent of (2x+3) is 1 so multiplicity =1
Now we set (x-1)^2 =0
take square root on both sides
x-1 =0
add 1 on both sides
x=1
For (x-1)^2 the exponent is 2
So multiplicity = 2